2020
DOI: 10.1038/s41598-020-69857-4
|View full text |Cite
|
Sign up to set email alerts
|

High spatially sensitive quantitative phase imaging assisted with deep neural network for classification of human spermatozoa under stressed condition

Abstract: Sperm cell motility and morphology observed under the bright field microscopy are the only criteria for selecting a particular sperm cell during intracytoplasmic Sperm injection (icSi) procedure of Assisted Reproductive Technology (ART). Several factors such as oxidative stress, cryopreservation, heat, smoking and alcohol consumption, are negatively associated with the quality of sperm cell and fertilization potential due to the changing of subcellular structures and functions which are overlooked. However, br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…Figure A2 in Appendix A shows the variation of the diameter with the liposome refractive index, with downward bias as the refractive index increases. Finally, it has been shown that sub-diffraction structures can be associated with size underestimation due to the possible loss of high-frequency information during image detection [52].…”
Section: Discussionmentioning
confidence: 99%
“…Figure A2 in Appendix A shows the variation of the diameter with the liposome refractive index, with downward bias as the refractive index increases. Finally, it has been shown that sub-diffraction structures can be associated with size underestimation due to the possible loss of high-frequency information during image detection [52].…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative phase imaging (QPI) is a rapidly emerging label-free technique to reconstruct quantitative information related to the refractive index and local thickness of the specimens [1]. The experimental and computational advancement in QPI is being widely adopted for extracting quantitative information of various industrial and biological specimens such as an optical waveguide, stem cells, human red blood cells (RBC), tissue sections, sperm samples, and among others [2][3][4][5]. In the past few decades, various newly developed QPI techniques have been implemented to improve the spatial resolution, spacebandwidth, temporal phase sensitivity, acquisition rate, and spatial phase sensitivity of the system [1,[6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Thambawita et al [ 22 ] suggested a two-stage architecture, where an autoencoder was used to extract sperm image features, and the pre-trained Resnet-34 CNN was employed for predicting motility and morphology of sperm heads. Butola et al [ 23 ] used feedforward deep neural networks (DNNs) to recognize normal and stress-affected sperm cells. They achieved an accuracy of 85.6% on a dataset of 10,163 interferometric images of sperm cells.…”
Section: Introductionmentioning
confidence: 99%